Prewerbalne zachowania komunikacyjne dzieci z zespołem Cri du Chat w ocenie rodziców - Kamyk - Wawryszuk, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Cri du Chat syndrome (CdC) is a rare disease characterized, among others, by decreased muscle tone, microcephaly, and high palate; underdevelopment of the mandible, abnormal structure and laryngeal function (somatic symptoms) and disorders of psychomotor development and intellectual disability (psychomotor symptoms). These children have a varied level of functioning and most of them do not use verbal speech. Describing the problem of preverbal communication behaviors, the following elements were taken into account: the level of behavior in the primary communication, sensory, auditory communication, organization of behavior and signaling needs. The purpose of this article is to describe the pre-verbal behavior of children with Cri du Chat syndrome. The following questions were formulated: What is the level of pre-verbal communication (primary, sensory and auditory) of a child with CdC syndrome? What are the communicative behaviors of the child with the CdC team and at what level of organization? What is the level of signaling your needs by a child with CdC? The preverbal communication behavior of children with the Cri du Chat team presented in the article indicate that they are diverse, ranging from indicating the gesture of what they need, to vocalizing in order to provoke contact with another person. The behavior of the daughter / son indicated by the parents may constitute the basis for the teaching process of preverbal communication.